Evaluasi Program SQUAD Dewan : Suara Kita untuk Demokrasi di Provinsi Jawa Timur - Alif Fitriana Effendi; Eny Haryati; Widyawati Widyawati (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
This research aims to evaluate the SQUAD Dewan (Suara Kita Untuk Demokrasi/Our Voice for Democracy) program implemented by the Secretariat of East Java Provincial Legislative Council (DPRD). The SQUAD Dewan program is an innovative initiative designed to enhance public participation in the legislative process and strengthen democratic practices at the provincial level. Using the CIPP (Context, Input, Process, Product) evaluation model developed by Stufflebeam, this study examines the program's effectiveness, efficiency, and sustainability. This qualitative research employs a descriptive approach, with data collected through in-depth interviews, focus group discussions, observation, and documentation at the Secretariat of the DPRD of East Java Province. Informants include program managers, legislative council members, public participants, and community representatives. The results indicate that the SQUAD Dewan program has successfully increased public engagement in legislative activities, with a 45% increase in public hearing participation and 60% growth in policy input submissions from 2022 to 2023. The program has effectively utilized digital platforms for broader outreach, reaching over 150,000 citizens through online forums and social media campaigns. However, challenges remain in terms of geographic coverage inequality, limited participation from rural communities, and the need for more sustainable funding mechanisms. This study recommends strengthening digital infrastructure in rural areas, developing capacity-building programs for community facilitators, establishing permanent funding allocations, and creating feedback mechanisms to enhance program responsiveness to public needs.